Consumer perspectives on personal recovery and borderline personality disorder. Issue 6 (6th November 2017) - Donald, Fiona; Duff, Cameron; Broadbear, Jillian; Rao, Sathya; Lawrence, Katherine
Abstract : Purpose: Borderline personality disorder (BPD) is a complex condition characterized by a number of psychosocial difficulties that typically involve considerable suffering for individuals with the condition. Recovery from BPD may involve specific processes such as work on how the self is perceived by the individual with BPD and his or her relationships which differ from those common to recovery from other mental health conditions. The details of the processes that may best promote changes within the self and relationships are yet to be established. The paper aims to discuss these issues. Design/methodology/approach: In total, 17 consumers from a specialist BPD service were interviewed to identify factors they have experienced that contribute to recovery from BPD. Thematic analysis within a grounded theory framework was used to understand key themes within the interview data. The emphasis was on specific conditions of change rather than the more global goals for recovery suggested by recent models. Findings: Key themes identified included five conditions of change: support from others; accepting the need for change; working on trauma without blaming oneself; curiosity about oneself; and reflecting on one's behavior. To apply these conditions of change more broadly, clinicians working in the BPD field need to support processes that promote BPD-specific recovery identified by consumers rather than focusing exclusively on the more general recovery principles previously identified within the literature. Originality/value: The specific factors identified by consumers as supporting recovery in BPD are significant because they involve specific skills or attitudes rather than aspirations or goals. These specific skills may be constructively supported in clinical practice.